Progressive Collapse Mechanism Analysis of Concrete-Filled Square Steel Tubular Column to Steel Beam Joint with Bolted–Welded Hybrid Connection - Wang, Jing-Xuan; Yang, Yong; Xian, Wei; Li, Qiu-Ying (International journal of steel structures, 2020)
When vertical load-bearing members of building structures are subjected to accidental loadings, such as an earthquake, fire or explosion, the remaining structure chiefly relies on the beam mechanism and catenary mechanism of the steel beam as the main resistance capacity, to prevent local or large-scale progressive collapse. This paper presents a three-dimensional finite element model of concrete-filled square steel tubular (CFST) column to steel beam joint with bolted–welded hybrid connection in a middle-column-removal scenario using ABAQUS software. The multi-scale modeling method was employed to calculate the collapse resistance and mechanism under vertical load. The vertical displacement and bearing capacity curve of the middle failure column was calculated and analyzed. The collapse mechanism and bearing capacity contribution of the steel beam tying in different directions are also discussed. Results indicate that the failure mechanism of the process includes the beam mechanism, the translation mechanism, the catenary mechanism and the failure stage. After the short-span steel beam had been destroyed, the long-span steel beam continued to provide collapse resistance capacity. To improve progressive collapse resistance, the CFST column to steel beam joint with welded haunch is proposed in this paper. Comparing the anti-collapse bearing capacity and failure characteristics of the joint with the welded haunch and common joint indicates that the anti-collapse capacity of the joint with welded haunch can be improved, and the research results can be referenced for engineering progressive collapse design.